Academic Publishing : Issues and Challenges in the Construction of Knowledge / Ken Hyland. - Hyland, Ken (Oxford applied linguistics., 2015)
The author discusses the impact of English as a global academic language The growth of the assessment culture surrounding publication The practices of knowledge construction at institutional and local levels The emergence of Open Access and social media publishing.